High dose intravitreal ganciclovir injection provides a prolonged therapeutic intraocular concentration. Issue 3 (March 1996) - Morlet, N; Young, S; Naidoo, D; Graham, G; Coroneo, M T
Abstract : BACKGROUND: Although intravitreal high dose ganciclovir has previously been found to provide excellent control of cytomegalovirus (CMV) retinitis, little was known about the vitreous concentrations of ganciclovir after a 2 mg intravitreal injection. METHODS: Eleven vitreous samples were taken from seven patients with CMV retinitis at 24 and 72 hours after a 2 mg intravitreal injection of ganciclovir and the concentration of ganciclovir was measured by high performance liquid chromatography. RESULTS: The mean concentration of ganciclovir at 24 hours was 143.8 mg/l (95% confidence interval 97.8-190) and at 72 hours was 23.4 mg/l (95% CI 0-49.7). The half life ranged from 11.9 to 26.3 (mean 18.8) hours in the four patients who had two samples taken. The mean half life calculated from the mean concentrations at 24 and 72 hours was 18.3 hours, so the calculated mean concentration at 7 days was 0.6 mg/l. CONCLUSIONS: This suggests that it takes about 7 days to eliminate the intravitreal ganciclovir, and that it is not likely to accumulate with weekly injections. The intravitreal concentrations achieved with high dose therapy remained above the ID50 for CMV (0.25-1.22 mg/l) for up to 7 days.